Проблема языковой ситуации в Испании - Даниленко, А.А. (Культура народов Причерноморья, 2014)
В статье рассматривается проблемные вопросы языковой ситуации в Испании,
представлены признаки национального варианта испанского языка, территориального варианта и
территориального диалекта испанского языка. Кроме того, дан анализ официальных языков
представленных на территории Испании помимо испанского языка (кастильского) – каталонский,
валенсийский, баскский, аранский и галисийский. На основе представленной характеристики
официальных языков Испании, а также их диалектов, все данные были структурированы в виде сводной
таблицы, которая свидетельствует о многообразии форм разновидностей испанского языка, его
национальных вариантов и диалектов. У статті розглядається проблемні питання мовної ситуації в Іспанії, представлені ознаки
національного варіанту іспанської мови, територіального варіанту і територіального діалекту. Крім
того, надано аналіз офіційних мов представлених на території Іспанії крім іспанської мови
(кастільської) - каталонська, валенсійська, баскська, аранська і галісійська. На основі представленої
характеристики офіційних мов Іспанії, а також їх діалектів, всі дані були структуровані у вигляді
зведеної таблиці, яка свідчить про різноманіття форм різновидів іспанської мови, його національних
варіантів і діалектів. The article deals with the problematic issues of the language situation in Spain. Currently, much
attention is devoted to problems of Spanish bilingualism. Spanish language has the official status alongside
English in a developed country such as the United States. Most Spanish speakers live in Latin America,
including Mexico, which occupies a leading position in the number of carriers of the Spanish language as their
mother tongue. At the national level, Spanish is the official language in Argentina, Bolivia, Chile, Colombia,
Costa Rica, Cuba, Dominican Republic, Ecuador, El Salvador, Guatemala, Honduras, Mexico, Nicaragua,
Puerto Rico, Panama, Paraguay, Peru, Uruguay and Venezuela. Spanish (Castilian) language is the most
common in Spain. Spain is not a multilingual state. Central government departments officially do not recognize
bilingualism, such as in Canada or Belgium. The exceptions are the institutions that are in areas where regional
languages are official. Translation of all state documents published in the official language of another region
into Spanish language is obliging. For example, a document published in Catalan in Barcelona and directed to
Palma de Mallorca (Balearic Islands), where Catalan is an official, must be translated into Spanish (Castilian)
by the public authorities, from which it is based. In Spain, the status of an official language in addition to
Castilian language also has some national regions - Catalan, Valencian, Basque, Galician and Aran. The article
describes these regional languages and presents them in a table, together with the dialects of Spanish language.
The material presented suggests that the existing forms of the Spanish language in Spain is very varied and in
each region and province there are many its variants. Thus, it is very difficult to cover all forms of the Spanish
language diversity, its national variants, dialects and sub-dialects and it requires further study and analysis.